Comportamento mecânico e de inflamabilidade do compósito de poliuretana derivada de óleos vegetais (PU) reforçado com fibra de algodão e alumina tri-hidratada - Silva, Amanda Albertin Xavier da (2018)
The present work consists in the evaluation of the mechanical and flammability behavior of the laminate composite of polyurethane derived from a blend of vegetable oils (PU) reinforced with cotton fiber fabric (CF) and with the addition of Alumina Trihydrate (ATH), as flame retardant. The manufacturing process used to obtain the composite is the vacuum bag. Composite specimens with different orientations of the fibers (from 0º, ± 45º, 90º) were produced. For the purpose of comparison and study, all materials were characterized separately, being pure PU, PU with addition of 10%, 20% and 30% of ATH, composite of PU reinforced with CF (PU+7CF) and composite of PU reinforced with CF and with ATH (PU+30%ATH+7CF). The mechanical behavior of these was evaluated according to tensile and flexure tests. With addition of ATH in the polyurethane there was a reduction in tensile and flexural strength, an increase in the modulus of elasticity and in the flexural modulus and a reduction in the Poisson ratio, proportional to the amount of alumina trihydrate that was applied, 10%, 20% and 30% of the total mass, the higher the amount of ATH more fragile and rigid the PU becomes. The composite of PU reinforced with CF (PU+7CF-0°) exhibited considerable growth at the maximum tensile strength (79 MPa), modulus of elasticity (3.7 GPa) was practically double that of pure PU (40 MPa and 1.7 GPa). The maximum flexural load of the composite of PU+7CF-0 ° (48.379 MPa and 1.530 GPa) exhibited a reduced value compared to pure PU (57.903 MPa and 1.530 GPa). For the composites of PU+30%ATH+7CF with orientation at 0°, the maximum tensile stress was 60 MPa and the modulus of elasticity (4.7 GPa) was practically double in relation to PU+30%ATH (2.6 GPa), matrix used for the manufacture of this composite. The flexural strength of the PU+30%ATH+7CF-0 ° (64.450 MPa) laminate was increased compared to the matrix applied therein, PU+30%ATH (48.734 MPa), different from the PU+7CF-0° composite. For samples with fibers oriented at ±45°, the composite of PU+7FA exhibited a shear modulus of 0.888 GPa and the maximum shear stress of 16.399 MPa and for the composite of PU+30%ATH+7CF was 0.902 GPa and 9.233 MPa, respectively. In relation to the vertical and horizontal flammability tests, none of the tested materials could be classified as self-extinguishable, but the ATH was efficient in reducing the speed of flame propagation. The Scanning Electron Microscopy (SEM) made it possible to evaluate the fiber-matrix interface of the composites, when ATH was added to the composite, there was a decrease in the fiber-matrix interface quality, presence of voids and larger occurrences of pull out, which explains, besides a smaller volumetric fraction of reinforcement exhibited, decrease in tensile strength in the composites of PU+30%ATH+7CF.